Institutional Mechanisms for Enhancing the Evaluation of Doctoral Research Outputs at Makerere University for Uptake and Use - Deboru, Florence; Etomaru, Irene (East African Journal of Education Studies, 2024)
Increasing emphasis is currently put on doctoral education as a source of capacity for innovation and socio-economic development worldwide. The purpose of doctoral research has been re-expressed and expanded in terms of not just its academic value, but its wider societal value. As such universities have an obligation to enhance the uptake and use of doctoral research outputs in other sectors. We examined the institutional mechanisms for enhancing the evaluation of doctoral research at Makerere University using the research knowledge infrastructure (RKI) framework as the analytical lens. We sought to answer the broad question: Do the institutional mechanisms for evaluating doctoral research at Makerere University facilitate the uptake and use of doctoral research outputs in other sectors? Subscribing to constructivist philosophy and interpretivist worldview, we used the qualitative single case study research design. We collected data through interviewing and review of documents. We interviewed 10 doctoral program coordinators, three research and graduate training managers and 13 PhD students we purposively. We reviewed seven institutional documents pertaining to graduate training at Makerere University: two plans, three policies, one framework and one guideline. We used thematic data analysis to make sense of the data. The findings revealed that institutional mechanisms to enhance the evaluation of doctoral research in terms of its potential for uptake and use were not well developed and integrated as part of doctoral research evaluation. We conclude that doctoral research evaluation at Makerere University was narrow and purely academic, limited to measures of scholarly rigour only. This limits the possibility for uptake and use of doctoral research outputs in other sectors. We recommend that the Directorate of Research and Graduate Training (DRGT) should develop expanded and comprehensive measures and indicators for evaluating doctoral research to enhance the uptake and use of doctoral research outputs beyond academia.